Comprehensive assessment to reveal the salt tolerance potential of cultivated eggplants and their wild relatives - Cebeci, Esra; Boyaci, Hatice Filiz; Kiran, Sevinc; Ellialtioglu, Sekure Sebnem (Frontiers in Plant Science, 2025)
This study aimed to uncover salt-tolerant eggplant (Solanum melongena L.) genotypes and accessions. Crop wild relatives (S. macrocarpon L., S. linnaeanum, S. incanum L., S. insanum L., S. sisymbriifolium Lam.), commercial varieties (Topan374, Kemer, Amadeo, Faselis, Bildircin), and local genotypes (TB, BB, MK, AH) were investigated under 150 mM NaCl stress. The experiment was set in a completely randomized block design with three replications. Morphological and biochemical parameters were studied to distinguish salt-tolerant genotypes. Wild relatives have species-specific growth features; thus, the salt tolerance levels of morphologic features such as plant height and leaf area were found inappropriate to be compared. In eggplant, Na+ is a majorly harmful ion and there is a negative correlation between leaf Na+ content and plant tolerance index. The low Na+ concentration in roots of BB and S. linnaeanum caused high K+ and Ca2+ concentrations in their leaves. A plant with high proline accumulation displays greater tolerance under stress conditions. The proline content of S. linnaeanum, S. incanum L., and MK was analyzed to be higher than the others. Additionally, the lowest malondialdehyde (MDA) increases were observed in S. linnaeanum, TB, and S. incanum L. Moreover, positive correlations were spotted between 0-5 scale values and MDA and Na+ level in shoots by correlation analysis. Strong correlations between proline accumulation–S. linnaeanum and MDA accumulation–AH were revealed by principal component analysis (PCA). In terms of results, the most salt-tolerant, S. linnaeanum, S. incanum L., BB, and MK, will be employed in future breeding studies to improve salt-tolerant inbred lines and varieties through interspecific hybridization.